Measurement of Exhaled Carbon Monoxide Levels in Patients Visiting to Dental Hospitals - Somana B. Vyshnavi; M. Shanthi; V. C Divya; C. Ganesh; Shreya Gupta; Korukonda Jayavardhan (Wolters Kluwer Medknow Publications, 2024)
Background: Nowadays, analyzing the amount of carbon monoxide in exhaled air is a commonly used method in population research and useful as a quantitative breathing guide and for verifying claims of not smoking. The primary and most prevalent indoor source of carbon monoxide is cigarette smoke. Objectives: To measure exhaled carbon monoxide levels in order to assess individual smoking status. Materials and Methods: An instantaneous, noninvasive way to determine smoking status may be offered by measuring carbon monoxide exhaled. A carbon monoxide analyzer or smoke analyzer (md diagnostics ltd, England) is a portable carbon monoxide analyzer and was utilized in this study to examine the exhaled carbon monoxide levels in established smokers and nonsmokers. The carbon monoxide levels exhaled were measured in 126 subjects (42 smokers, 42 smokeless tobacco, 42 nonsmokers) visiting a dental hospital. Results: The Mean exhaled carbon monoxide level was 1-6 PPM for nonsmokers, 7-20 PPM for smokers, and 3-18 PPM for smokeless tobacco users. Conclusion: The level of carbon monoxide in exhaled air or as blood carboxyhemoglobin yielded higher specificity and sensitivity. To summarize, the exhaled carbon monoxide level offers a quick and simple method for determining a person's smoking status.